Perilaku pencarian informasi dalam menyelesaikan tugas akhir mahasiswa prodi manajemen pendidikan islam (mpi) angkatan 2019 uin maulana malik ibrahim malang menggunakan ellis model - maulidia, suci (Maliki Interdisciplinary Journal, 2025)
Information is a fundamental necessity for individuals, especially students, in supporting academic activities such as research and thesis writing. Technological advancements have facilitated information access but also present challenges in terms of source validity and relevance. This study analyzes the information-seeking behavior of students in the Islamic Education Management (MPI) program, class of 2019, at UIN Maulana Malik Ibrahim Malang by applying the Ellis Model. This model comprises the stages of Starting, Chaining, Browsing, Differentiating, Monitoring, Extracting, Verifying, and Ending to understand systematic information-seeking strategies. The findings indicate that students face challenges in the Browsing and Chaining stages due to limited access and difficulties in finding relevant information. However, by implementing effective search strategies, students can enhance the validity and accuracy of the data used. This study provides insights into optimizing academic information-seeking processes and offers recommendations for students and institutions to improve access and the quality of information sources.